Case Report and review of literatures Common Carotid Artery Aneurysm and Subclavian Arterio-Venous Fistula - Hussen, Waleed M. (Journal of the Faculty of Medicine Baghdad, 2009)
Vascular injury is still common in countries such as Iraq where both military and urban violence are endemic.This is a report of a thirty eight year old civilian patient who had been inflicted with shrapnel injury during the 3rd. Gulf war, which had caused two different types of vascular injury with minimal evidence of vascular injury with evidence of only two small wounds in the neck and upper chest at the time of injury but presented few months later with a pulsatile neck mass and palpable thrill across the right supraclavicular area and upper chest.Preoperative investigations were done including Doppler study and angiography which confirmed the presence of right common carotid artery aneurysm and right subclavian arterio- venous fistula.Surgical treatment performed sixteen months later by combined trap-door approach and cervical incisions and by the use of scrubner's shunt (which is used for emergency haemodialysis in renal failure patients) as a carotid shunt due to the unavailability of carotid shunt in Iraq to maintain cerebral perfusion during common carotid artery clamping .Excellent recovery occurred without any neurological sequel.The report will include also a review of literatures about these rare vascular injuries.